The impact of the shortage of educational supervisors in the Jerusalem Education Directorate on the quality of teaching - Atoun, Dima Yousef; Arman, Ibrahim (Journal of Educational and Psychological Sciences, 2024)
The aim of this study was to determine the need for educational supervisors in the schools of the Jerusalem Directorate to guide and develop teachers, and to identify the supervisory areas lacking among teachers in the Jerusalem Directorate schools. The researchers relied on a qualitative approach focusing on describing and interpreting social phenomena to understand the experiences, expertise, and concepts related to the research topic. The study population included all teachers in Al-Awqaf schools and private schools in the Jerusalem Directorate of Education. This study was conducted during the second semester of the academic year (2023/2024), where the researchers built an interview tool to explore teachers’ feelings and thoughts about the shortage of educational supervisors and its impact on the quality of their teaching. The results of data analysis and coding revealed three main axes constituting "the need for educational supervisors to guide and develop teachers": dissatisfaction with the shortage of educational supervisors, the need for monthly visits to teachers by supervisors, and the importance of caring for new teachers. It also revealed teachers’ need for continuous classroom visits, training courses, and workshops. Finally, the shortage of educational supervisors affects the quality of teaching, so there is a need to enhance continuous communication and organize workshops and training courses to activate the role of the school principal as a resident supervisor.